2017
DOI: 10.1097/aln.0000000000001631
|View full text |Cite
|
Sign up to set email alerts
|

Management of Severe Bleeding in Patients Treated with Direct Oral Anticoagulants

Abstract: Background The use of prothrombin complex concentrates and the role of plasma concentration of anticoagulants in the management of bleeding in patients treated with direct oral anticoagulants are still debated. Our aim was to describe management strategies and outcomes of severe bleeding events in patients treated with direct oral anticoagulants. Methods We performed a prospective cohort study of 732 patients treated with dab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 35 publications
3
44
0
3
Order By: Relevance
“…A recent study by Song et al suggested that 50 IU/kg PCC was effective in reversing the anticoagulant action of apixaban as well [26]. e efficacy of PCCs on clinical outcomes on patients with NOACs and active bleeding is not yet established in a randomized control trial although observational studies are suggestive of efficacy in achieving hemostasis [27]. e European Heart Association recommends the use of PCC or aPCC in the absence of specific reversal agents in patients with major bleeding.…”
Section: Nonspecific Reversal Agentsmentioning
confidence: 99%
“…A recent study by Song et al suggested that 50 IU/kg PCC was effective in reversing the anticoagulant action of apixaban as well [26]. e efficacy of PCCs on clinical outcomes on patients with NOACs and active bleeding is not yet established in a randomized control trial although observational studies are suggestive of efficacy in achieving hemostasis [27]. e European Heart Association recommends the use of PCC or aPCC in the absence of specific reversal agents in patients with major bleeding.…”
Section: Nonspecific Reversal Agentsmentioning
confidence: 99%
“…Nonspecific hemostatic agents such as recombinant factor VII, factor VIII inhibitor bypassing activity, or PCCs have been suggested based on clinical need. [321][322][323] A dabigatran-directed neutralizing antibody, idarucizumab, has been approved for use. A prospective study showed that idarucizumab normalized the elevated ECT in 88% to 98% of patients, an effect that was seen within minutes.…”
Section: Dabigatranmentioning
confidence: 99%
“…344 Nonspecific hemostatic agents, including recombinant factor VII and PCCs, may be used to reverse the NOACs. [321][322][323] Andexanet is a recombinant modified human factor Xa decoy protein that binds and sequesters factor Xa inhibitors within the vascular space, restoring the factor Xa activity. A 2-part randomized, placebo-controlled study was recently conducted in older healthy volunteers.…”
Section: Rivaroxabanmentioning
confidence: 99%
“…In such situations, percutaneous or surgical left atrial appendage occlusion may be considered as a valuable option instead of long-term anticoagulation [1,4,100]. Finally, whether the use of PCC or aPCC is useful in NOAC-related intracranial bleeding is still hotly debated [101][102][103][104] since a multicentre analysis did not reveal a significant benefit on hematoma enlargement [105]. In patients with intracranial bleeding caused by dabigatran, reversal of the anticoagulant effect is possible by infusion of reversal agent, idarucizumab.…”
Section: Life-threatening Bleedingsmentioning
confidence: 99%